Effect of Climate Change-Driven Tidal Dynamics on The Stability of Senggarang Coastal Embankment - BIN ABDUL AZIZ, MUHD KHAIRUL IKHWAN; CHEE MING, CHAN (Progress in Engineering Application and Technology, 2022)
Coastal areas can be described as one of the areas that where it is environmentally sensitive where the ecosystem and local inhabitants may be exposed to some threats such as erosion. Wave erosion and flooding during and after large tidal events were serious risks to the Malaysian coastline in 2000. The Senggarang embankment is facing severe seepage phenomena which could lead to collapse and critical flooding risk where rising sea level is happen. The seepage problem has severely compromised the stability and safety of the embankment, especially where the inland area is flooded during tide. Hence, this study will focusing on the climatic factor that leads to the problem. The objectives of this research are to examine the tidal dynamics for the past decade at Senggarang Coastal Embankment (SCE) in relation with climate change via analysing data from past case study and literature review and to developed the Failure Risk Assessment tool for Senggarang Coastal Embankment (SCE) due to the sea level assessment and projection using Plaxis.. In this study, the embankment was modelled by the use of PLAXIS software program. PLAXIS 8 is a finite elements package used for the two-dimensional analysis of deformation and stability in geotechnical engineering. In summary,it was found that discharge of seepage for embankment constructed with original condition of embankment and present condition of embankment. The projection of mean sea level also being plotted in a graph and being analyze accordingly. The higher the water level, the higher the discharge of seepage. Rising in sea level seems to lower the strength of the embankment by increase in displacement, effective stress, excess pore pressure and seepage. Therefore, climatic factor does lead to failure of Senggarang embankment.